Компресійний синдром за шийно-медіастинальної локалізації патологічно зміненої щитоподібної залози - Висоцький, А. Г.; Сидоренко, Ю. О.; Гюльмамедов, С. І.; Сагалевич, А. І.; Чірков, Ю. Е. (Clinical Endocrinology and Endocrine Surgery, 2008)
In work the retrospective analysis of diagnostic researches and results of surgical treatment is conducted 85 patients with pathology of thyroid of substernal localization, operated from 2003 to 2007 years. With the purpose of receipt of objective information about the degree of compression of organs of neck and top medyastynal, the coefficient of closed of overhead pectoral aperture expected from information of computer tomography is offered. Authenticity of the last is confirmed by the lung function information and ultrasonic full-duplex scanning of vessels of neck.